Efferocytosis-related gene IL33 predicts prognosis and immune response and mediates proliferation and migration in vitro and in vivo of breast cancer - He, Xiao; Cheng, Xianjie; Zhang, Zhun; Chen, Lanhui; Xie, Changjun; Tang, Mengjie (Frontiers in Pharmacology, 2025)
BackgroundBreast cancer (BRCA) has a high incidence among women, with poor prognosis and high mortality, which is increasing year by year. Efferocytosis is a process of phagocytosis of abnormal cells and is of great value in tumor research. Our study seeks to create a predictive model for BRCA using efferocytosis-related genes (ERGs) to explore the significance of efferocytosis in this disease.MethodsIn this research, Differential analysis, and univariate Cox regression were employed to identify genes linked to prognosis in BRCA patients. Then the BRCA patients were categorized into distinct groups using consensus clustering based on prognosis genes. Survival analysis, PCA, and t-SNE were performed to verify these groups. The enrichment of metabolic pathways within the detected clusters was evaluated using gene set variation analysis (GSVA) and gene set enrichment analysis (GSEA). Additionally, single-sample GSEA (ssGSEA) was used to examine changes in immune infiltration and enrichment. A risk prognostic model was constructed utilizing multivariable Cox regression and Least Absolute Shrinkage and Selection Operator (LASSO) analyses, and subsequently validated its predictive accuracy by stratifying patients according to the median risk score. Ultimately, some crucial independent prognostic genes were pinpointed and their expression, roles, and immune characteristics were explored in both laboratory and live models.ResultsFindings revealed 52 differentially expressed genes (DEGs), of which 21 were significantly linked to BRCA outcomes. These 21 genes were utilized for consensus clustering to categorize BRCA patients into two subtypes. Subtype B was linked to a worse prognosis compared to Subtype A, though both subtypes were distinguishable. The enriched pathways were mainly concentrated in Subtype A and were actively expressed in this group. Following this, a prognostic risk model was constructed using five risk genes, which was proven to possess significant predictive value. A significant link was identified between the immune microenvironment and the risk-associated genes and scores. IL33 was identified as an independent prognostic gene with important research value. Its in vivo expression results aligned with the data analysis findings, showing low expression in BRCA. Furthermore, overexpression of IL33 significantly inhibited BRCA growth and motility in vitro and in vivo, while also enhancing their vulnerability to destruction by activated CD8+ T cells.ConclusionThe ERG-based risk model effectively predicts the prognosis of BRCA patients and shows a strong link with the immune microenvironment. IL33 stands out as a significant prognostic marker, crucial in the onset and advancement of BRCA. This highlights the necessity for additional studies and indicates that IL33 might be a potential target for BRCA treatment.